PENGARUH MORALITAS INDIVIDU, EFEKTIVITAS PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI DAN ASIMETRI INFORMASI TERHADAP KECURANGAN AKUNTANSI - Siti Rachmah Citra Amelia; Teti Rahmawati (Program Studi Akuntansi, Universitas Kuningan, 2021)
This study aims to examine the effect of individual morality, effectiveness of internal control, suitability of compensation and information asymmetry on accounting fraud. This research was conducted using descriptive and verification methods. The population of this study were all villages in Kramatmulya District, Jalaksana District, Cigandamekar District and Cilimus District in Kuningan Regency as many as 53 villages with a total of 159 respondents. The sample used in this study were 38 villages with a total of 114 respondents using Propotional Sampling. The data collection technique used a questionnaire with data analysis tools in the form of multiple linear regression analysis. The results of this study indicate that individual morality, internal control effectiveness, compensation suitability and information asymmetry have a simultaneous effect on accounting fraud, individual morality has a significant negative effect on accounting fraud, the effectiveness of internal control has a significant negative effect on accounting fraud, compensation suitability has a significant negative effect on accounting fraud and asymmetry information has a significant positive effect on accounting fraud. Keywords: Individual Morality, Effectiveness of Internal Control, Compensation Suitability, Information Asymmetry and Accounting Fraud.